Analysis of antioxidant activity of carrots (Daucus carrota L.) using FRAP and CUPRAC methods - Aprilya Sri Rachmayanti; Nurmaya Effendi; Andi Muflihunna (Universitas Muhammadiyah Malang, 2021)
Carrot antioxidant activity analysis has been carried out. Carrot juice was analyzed qualitatively by the FRAP method using FRAP reagent and by the CUPRAC method using copper (II) chloride solution, neucuproine solution, ammonium acetate buffer solution, and distilled water. Quantitatively, the mixture of sample solutions using the FRAP and CUPRAC methods was analyzed using a UV-Vis spectrophotometer at a wavelength of 596 nm for the FRAP method and 452 nm for the CUPRAC method, using Trolox solution as the standard curve. The results obtained were that each sample A and B's antioxidant activity using the FRAP method was 0.5186 µM TR/g and 0.8857 µM TR/g samples. Meanwhile, samples A and B's antioxidant activity using the CUPRAC method was 0.1160 µM TR/g sample and 0.1762 µM TR/g sample.